Literature Review of Primary Care Interventions to Prevent Child Maltreatment - Muhammad Ikhsan, Muhammad Ikhsan; Farah, Farah (The Indonesian Journal of General Medicine, 2024)
Background: The literature on primary care interventions aimed at preventing child maltreatment reveals a complex interplay between risk factors, intervention strategies, and the need for tailored approaches to support families. Literature Review: The examination of primary care interventions aimed at preventing child maltreatment reveals a multifaceted landscape characterized by varying risk factors, intervention strategies, and the necessity for tailored approaches to effectively support families. The literature emphasizes the challenges in developing universal strategies that cater to the diverse circumstances of families while ensuring that interventions are perceived as personalized. A significant gap exists in the current research regarding effective interventions for families facing multiple stressors, such as substance abuse and domestic violence, highlighting the need for a preventative public health approach that enhances awareness of child maltreatment signs. Conclusion: Collectively, these articles underscore the importance of a multifaceted approach to child maltreatment prevention, advocating for tailored interventions that address the unique challenges faced by families. The literature highlights the necessity for continued research to inform effective practices within primary care contexts, focusing on the integration of behavioral parenting interventions to address the broader implications of parenting practices on child development and well-being.